Impacts of Aquaponics Gardening on Weight Management of Undernourished Children - Cruz, Mikylla Lorraine; De Jesus, Regie P.; Arcojo, Airone A.; Hernandez, Jack Ivan A.; Yanson, Peterson J.; Siosana, Luther S. (Al-Hijrah Indonesia, 2025)
Background: Malnutrition remains a major concern among children in disadvantaged communities in the Philippines. This study examined the effectiveness of aquaponics gardening in supporting weight management and promoting healthy eating among undernourished children. Methods: A quasi-experimental pre-test–post-test design was implemented with 30 children aged 6–12 years in Bocaue, Bulacan, identified as undernourished (BMI-for-age < 5th percentile). Over eight weeks, subjects engaged in aquaponics gardening, nutrition education, and meal preparation using harvested produce. Data were gathered through BMI measurements, a validated Likert-scale survey, and 24-hour dietary recalls. Paired t-tests evaluated pre- and post-intervention changes. Results: Significant improvements were observed in weight (23.4 kg to 25.1 kg) and BMI (13.5 to 14.3) (p < 0.001). Subjects also demonstrated greater nutritional knowledge, more positive perceptions of vegetables, and healthier eating behaviors, including increased vegetable intake. Conclusion: Aquaponics gardening is a feasible, sustainable approach to improving child nutrition and dietary habits. Its hands-on design fosters learning and self-efficacy, supporting long-term food security and health promotion in low-resource communities.